2013
DOI: 10.1158/1535-7163.mct-12-0983-t
|View full text |Cite
|
Sign up to set email alerts
|

Developing Lipid Nanoparticle-Based siRNA Therapeutics for Hepatocellular Carcinoma Using an Integrated Approach

Abstract: Successful siRNA therapeutics requires the optimal integration of multiple components, including an efficient delivery system, a disease indication that is appropriate for siRNA-based therapy, and a potent and nontoxic siRNA against a robust therapeutic target. Although all currently available delivery systems have limitations, it is important to recognize that a careful selection of the disease indication, therapeutic target, and siRNA molecule could partially compensate for deficiencies associated with the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…In this study, we confirmed by in vitro experiments that expression of APOE is a major determinant of Patisiran-mediated knockdown. Human hepatoma cell line HepG2 was chosen which was previously used to evaluate other siRNAs and various LNP formulations [19,20]. Our data indicate that downregulation of APOE significantly deteriorates silencing of TTR.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, we confirmed by in vitro experiments that expression of APOE is a major determinant of Patisiran-mediated knockdown. Human hepatoma cell line HepG2 was chosen which was previously used to evaluate other siRNAs and various LNP formulations [19,20]. Our data indicate that downregulation of APOE significantly deteriorates silencing of TTR.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, intratumoral VEGF expression was not reduced by VEGF-siRNA/DOTAP complexes but rather increased [129]. More recently, Shen et al screened several lipid NPs for optimal siRNA delivery to HCC and identified a combination of lipids that showed significant anti-tumor effect with cancer-targeting siRNA’s [130]. An interesting note in this study is that good in vitro transfection efficiency did not necessarily translate to good in vivo silencing effect in orthotopic HCC tumors, which indicates the significance of circulation stability of gene-carrier complexes [130].…”
Section: Pharmacological Effects Of Sirna Therapeuticsmentioning
confidence: 99%
“…11 Furthermore, the correlation between, and the relevance of results from in vitro and in vivo knock down experiments are much better understood, especially with respect to the impact of PEG shielding, and hence use for the modulation of PK properties critical for in vivo delivery. 12 We have previously reported on a newly synthesized cationic lipid, referred to as AtuFECT01, as part of the lipid system AtuPLEX, which exhibits more efficient siRNA binding activity and delivery to cells of the vascular endothelium as compared to other commercially available cationic lipids such as DOTAP or DOTMA. 5 Nevertheless, such nanoparticles tend to accumulate in filtering organs of the reticuloendothelial system.…”
Section: Introductionmentioning
confidence: 99%